Subtitling in crime TV shows and its barriers: a study of cultural and linguistic differences in the series "Law & Order" - Rosário, Talissa Barcelos; Lage, Gabriela Diehl (BELT - Brazilian English Language Teaching Journal, 2012)
This research compares the subtitling choices of three recurrent terms from the TV show Law & Order with the translations proposed by Noronha Legal Dictionary (2003), while narrowing the meaning of the terms selected according to the Penal Codes of both New York and Brazil. The purpose of this study is to point out the problems originated by the different Codes and different translation options, taking into consideration the limitations that this kind of media can bring to the translator (NOBRE, 2011). Venuti’s (2002) ideas of domestication and foreignization will also be used to show how the translation possibilities work in the translation system adopted. Finally, whether the translator decides to domesticate the terms to the Brazilian culture or to translate them literally, a full coherence and understanding of the whole system will hardly be achieved.